ANALISIS PERBANDINGAN METODE SIMPLE MARKET MODEL DAN METODE DIMSON (STUDI EMPIRIS PADA PERUSAHAAN LQ-45) - Intan Shaferi; Jaryono Jaryono (Faculty of Economics and Business Universitas Jenderal Soedirman, 2011)
Investors expect return in investment. They can predict expected return by applying CAPM. CAPM uses beta as risk measurement. Beta also shows stock’s sensitivity to market condition. Some methods have already taken by researchers to estimate better beta. In this study, simple market model or OLS and Dimson Method were used and compared. This study is aimed at finding fact that beta calculated by Dimson method can predict return more accurately than OLS. This research took place in Indonesian Stock Market using LQ-45 companies from 2004 to 2008. Analysis was done by using monthly return from 2004 to 2007 for formulating OLS and Dimson equation models. After getting two equation models, we have two betas from each equation. Then, those two betas are used for calculating CAPM for predicting return in 2008. The prediction of return then being compared with the actual return of 2008 to get MAD. This study used nine companies as sample and the result showed that five companies or 55 percent suggested that beta of Dimson method predicts more accurately return than OLS.